DYNAMICS OF TAX EVASION IN INDONESIAN SMES: TAX RATES, SELF-ASSESSMENT SYSTEMS, AND TAX MORALE - Widjaja, William; Michael, Michael (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
This study examines tax evasion among Indonesian MSMEs, focusing on tax rates, tax system complexity, and self-assessment. The quantitative survey included 100 Jakarta MSMEs. It finds that high tax rates increase tax evasion, which hurts MSMEs' competitiveness and growth. Due to low resources and distrust of government, tax evasion is unaffected by the complex tax system. However, the self-assessment method reduces tax avoidance by promoting transparency, accountability, and awareness among MSMEs. To regulate the self-assessment system and tax evasion, tax morale is vital. It impacts tax fairness and ethics. The findings stress the need for fair tax policy, streamlining tax procedures, and enhancing tax education to prevent tax evasion and boost long-term economic growth. Public confidence in government institutions and tax compliance is essential for MSMEs to thrive and contribute to the economy.